Bridging the gap of Inequity in Implementation Science: Adaptations of Group EBPs for those with Serious Mental Illness in the Public Sector. - Carr, Erika R. (Community Mental Health Journal, 2025)
There are many group EBPs that are now listed as effective treatments for those with serious mental illness (SMI). Despite this, there are few of these group EBPs that are being delivered consistently in the public sector, causing disparity. This article reviews the challenges that relate to implementation science and those with SMI receiving group EBPs to help them live a life of meaning as they define. The article discusses the need for adaptations of EBPs as individuals with complex concerns need different approaches to implementation science. Next, the article conveys what core constructs of group EBPs have to be maintained as they are and what elements of EBPs need adapting to empower those with SMI in engagement. This article provides knowledge of practical application of implementation science approaches while providing dialectical behavior group therapy and cognitive behavior group therapy for psychosis adaptations for those with SMI in a public sector inpatient setting.